2012
DOI: 10.1007/s10840-012-9707-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of left atrium appendage clot detection despite on-target warfarin prevention for atrial fibrillation

Abstract: We found a 2.3 % prevalence of LA thrombus (12.1 % when SEC was also considered). The thrombus was present despite on-target warfarin prevention. In addition to a higher CHA(2)DS(2)VASc score, a larger LA size was a strong predictor of clot detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
1
12
2
2
Order By: Relevance
“…This study has demonstrated a very low prevalence (0.6%) of LA/LAA thrombus in patients undergoing AF ablation. These results are consistent with other studies with similar cohorts of patients (mean age 57–60 years, majority (64–80%) male, all undergoing TOE prior to AF ablation, with similar anticoagulation protocols) who also found thrombus prevalence to be between 0.5% and 2.3% (9, 13, 14). …”
Section: Discussionsupporting
confidence: 91%
“…This study has demonstrated a very low prevalence (0.6%) of LA/LAA thrombus in patients undergoing AF ablation. These results are consistent with other studies with similar cohorts of patients (mean age 57–60 years, majority (64–80%) male, all undergoing TOE prior to AF ablation, with similar anticoagulation protocols) who also found thrombus prevalence to be between 0.5% and 2.3% (9, 13, 14). …”
Section: Discussionsupporting
confidence: 91%
“…Similar to the analysis of Gunawardene et al ., high CHADS 2 and CHA 2 DS 2 ‐VASc scores were found to be independent predictors of LAAT in multivariate analysis of previous studies as well . Puwanant et al.…”
mentioning
confidence: 71%
“…In the study by Wyrembak et al., no LAAT was found in NOAC treated patients with CHA 2 DS 2 ‐VASc score <5 or in warfarin treated patients with CHA 2 DS 2 ‐VASc score <2 . Zoppo et al . also found in multivariate analysis that a higher CHA 2 DS 2 ‐VASc scores predicted LAAT.…”
mentioning
confidence: 93%
See 2 more Smart Citations